Nisekoi : false love. Vol. 25, False love - Komi, Naoshi, 1986- (Shonen Jump manga., 2018)
Love triangle! Comedic antics!! Gang warfare?! You won't want to miss out on Shonen Jump's laugh-out-loud feel-good manga series! It's hate at first sight when Raku Ichijo first meets Chitoge Kirisaki. But much to their chagrin, the two are forced into a false love relationship to keep the peace between their feuding gangster families.